Perancangan Aplikasi Estimasi Harga Pokok Penjualan dan Produksi Berbasis Web - Nova Andriani; Jenie Sundari (Universitas Halu Oleo, 2021)
The speed of data transformation is very much needed in order to increase work and information needs. this is very much needed in all fields. especially in the industrial sector. we can use this growing technology for many things, to minimize errors and also make work easier. it is a pity if we can take advantage of existing technology but calculations and work are still done manually. therefore, in research this is designed a web-based application using php and mysql. with this application design, it is expected to be able to make work more effective and efficient. and in this sophisticated digital age, it would be better if we choose to reduce the use of paper. this can also save operational costs and a step to reduce global warming. and during a pandemic like this, it is very necessary to reduce face-to-face interactions. to reduce that interaction and make it easier to store data and search for data in making reports and calculating cost estimates,make it application design of web- based cost of goods sold and production estimation application.